2015
DOI: 10.1016/j.jnucmat.2014.11.064
|View full text |Cite
|
Sign up to set email alerts
|

Binary and ternary Po-containing molecules relevant for LBE cooled reactors at operating temperature

Abstract: Quantum-chemical calculations at several levels of theory were used to assess the stability at different temperatures of a set of 13 binary and ternary Pocontaining molecules that could possibly be formed in an environment with lead, bismuth, oxygen and water. These are conditions that are relevant for a heavy liquid metal cooled fission reactor. The conclusions are that especially PoPb, PbPoO and PoOH and to a lesser extent Po 2 and PoO are stable. These small molecules are likely to be found near the Lead-Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…In order to assess the level of theory that will be required, we compare in In ref. [25], it was already shown that PBE0 succeeds surprisingly well in reproducing the formation energies obtained by the much more accurate MRCI Whereas MRCI and PBE/PBE0 are in fair agreement with each other when 120 no spin-orbit interaction is included (Fig. 1a), this agreement vanishes upon adding spin-orbit coupling (Fig.…”
Section: Level Of Theorysupporting
confidence: 67%
See 2 more Smart Citations
“…In order to assess the level of theory that will be required, we compare in In ref. [25], it was already shown that PBE0 succeeds surprisingly well in reproducing the formation energies obtained by the much more accurate MRCI Whereas MRCI and PBE/PBE0 are in fair agreement with each other when 120 no spin-orbit interaction is included (Fig. 1a), this agreement vanishes upon adding spin-orbit coupling (Fig.…”
Section: Level Of Theorysupporting
confidence: 67%
“…More recently the formation of several polonium-containing 50 molecules, whose existence is expected in a LBE environment, has been studied in Van Yperen-De Deyne et al [25]. In the present work we use density functional theory (DFT) to examine the interaction between a low concentration of monoatomic polonium and the surfaces of the candidate filter materials palladium, silver, platinum and gold.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The results from SEARCH indicated that while DFT proved to be adequate to describe the adsorption interaction of monoatomic polonium with noble metal surfaces, it is not suitable for a reliable calculation of thermodynamic properties of polonium-containing molecules. [42] Therefore, a combination of more sophisticated methods had to be applied that properly account for electron correlation and the spin-orbit effects that are particularly important for heavy elements such as Pb, Bi and Po. The new calculation routine developed within MYRTE was proven to reliably predict temperature dependent thermodynamic properties of diatomic polonium-containing molecules.…”
Section: Recent Results: the Euratom H2020 Project Myrtementioning
confidence: 99%
“…Furthermore, a lower trapping temperature meant that the vapor could nucleate and grow on the nanofiber surface, even with a lower degree of subcooling, which also increased the nucleation rate and accelerated the deposition of vapor on the membrane surface. According to relevant studies, the vapor pressure of PbTe is between those of Pb and Bi, indicating that the volatility of PbTe is higher than that of pure Pb and lower than that of Bi [43][44][45][46]. Meanwhile, the melting point of Bi is much lower than that of PbTe; thus, a higher degree of subcooling can be achieved for PbTe.…”
Section: Phase and Structural Analysis Of Lbe-tementioning
confidence: 99%